Quranic Parenting Model Inspired by Prophet Zakaria: A Framework for Family Upbringing - Muhammad Zul Fahmi; Nur Fadhilah Syam (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study explores the Quranic parenting inspired by the story of Prophet Zakaria and its relevance to contemporary family upbringing. The research is motivated by the shift in modern parenting patterns, which often prioritize material fulfillment while neglecting consistent spiritual and moral development. Using a qualitative approach with descriptive-interpretative methods, data were collected through observation, interviews, documentation, and Quranic exegesis. The findings reveal that Prophet Zakaria’s parenting values emphasize sincerity in supplication, spiritual awareness, humility, hope for righteous offspring, transmission of religious values, and orientation toward divine approval. These values are reflected in practices such as habitual worship, Quran education, gentle parental advice, role modeling, and community involvement in religious activities. Nevertheless, challenges persist, including the influence of modernization, inconsistent parental practices, and limited religious understanding within families. The study concludes that the Quranic parenting model inspired by Prophet Zakaria provides a relevant framework for nurturing a generation that is faithful, ethical, and socially responsible.